Transcriptome Comparison Reveals Distinct Selection Patterns in Domesticated and Wild Agave Species, the Important CAM Plants. (22nd November 2018) - Huang, Xing; Wang, Bo; Xi, Jingen; Zhang, Yajie; He, Chunping; Zheng, Jinlong; Gao, Jianming; Chen, Helong; Zhang, Shiqing; Wu, Weihuai; Liang, Yanqiong; Yi, Kexian
Abstract : Agave species are an important family of crassulacean acid metabolism (CAM) plants with remarkable tolerance to heat and drought stresses ( Agave deserti ) in arid regions and multiple agricultural applications, such as spirit ( Agave tequilana ) and fiber ( Agave sisalana ) production. The agave genomes are commonly too large to sequence, which has significantly restricted our understanding to the molecular basis of stress tolerance and economic traits in agaves. In this study, we collected three transcriptome databases for comparison to reveal the phylogenic relationships and evolution patterns of the three agave species. The results indicated the close but distinctly domesticated relations between A. tequilana and A. sisalana . Natural abiotic and biotic selections are very important factors that have contributed to distinct economic traits in agave domestication together with artificial selection. Besides, a series of candidate unigenes regulating fructan, fiber, and stress response-related traits were identified in A. tequilana, A. sisalana, and A. deserti, respectively. This study represents the first transcriptome comparison within domesticated and wild agaves, which would serve as a guidance for further studies on agave evolution, environmental adaptation, and improvement of economically important traits.